2015
DOI: 10.1021/acs.nanolett.5b04361
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Potassium-Doped Metallic Polymorphs of MoS2

Abstract: Superconducting layered transition metal dichalcogenides (TMDs) stand out among other superconductors due to the tunable nature of the superconducting transition, coexistence with other collective electronic excitations (charge density waves), and strong intrinsic spin-orbit coupling. Molybdenum disulfide (MoS2) is the most studied representative of this family of materials, especially since the recent demonstration of the possibility to tune its critical temperature, Tc, by electric-field doping. However, jus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(132 citation statements)
references
References 60 publications
(246 reference statements)
8
118
1
Order By: Relevance
“…Figure S7 shows M / H – T plots at different H ’s, and the H – T phase diagram ( Figure S7 ) was constructed from the T c onset at each H ; the fitted curve indicates the H c2 at each temperature. The positive curvature seen in Figure S7 is similar to the behavior of (NH 3 ) y K x MoS 2 reported recently 21 . The H c2 at 0 K, H c2 (0), was evaluated to be 2.4 T. However, the data of the H c2 – T c plot are confined near T c .…”
Section: Resultssupporting
confidence: 88%
“…Figure S7 shows M / H – T plots at different H ’s, and the H – T phase diagram ( Figure S7 ) was constructed from the T c onset at each H ; the fitted curve indicates the H c2 at each temperature. The positive curvature seen in Figure S7 is similar to the behavior of (NH 3 ) y K x MoS 2 reported recently 21 . The H c2 at 0 K, H c2 (0), was evaluated to be 2.4 T. However, the data of the H c2 – T c plot are confined near T c .…”
Section: Resultssupporting
confidence: 88%
“…227,228 Molecular gates can also modulate the carrier type and density in 2D semiconductors more effectively than conventional electric field gating, which not only enriches p-type and n-type building blocks for electronic and optoelectronic devices, 226 but also introduces metallic 224,229 and superconducting behavior. 225,230 Many types of doping can be employed to engineer the properties of 2D materials. Substitutional doping in the 2D lattices can enable the formation of robust, stable alloys, where substituting atoms can be electron or hole donors to tune the free carrier type in semiconductors, e.g., Nb (hole donor) 7,239 and Re (electron donor) 180,240 in MoS2, which can result in degenerate doping.…”
Section: Doping and Alloyingmentioning
confidence: 99%
“…Other intercalants including Na, K, and ammonium ions have been employed to achieve the TMD phase transition [92][93][94][95]. It is demonstrated that appropriate intercalant concentration results in the phase transition, whereas the excessive concentration would lead to the structural degradation [92].…”
Section: Intercalationmentioning
confidence: 99%